2011
DOI: 10.1097/jto.0b013e31822e59b3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Computed Tomography Screening for Lung Cancer in the United States

Abstract: Introduction A randomized trial has demonstrated that lung cancer screening reduces mortality. Identifying participant and program characteristics that influence the cost-effectiveness of screening will help translate trial results into benefits at the population level. Methods Six U.S. cohorts (males and females aged 50, 60, or 70) were simulated in an existing patient-level lung cancer model. Smoking histories reflected observed U.S. patterns. We simulated lifetime histories of 500,000 identical individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
4
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(191 citation statements)
references
References 38 publications
5
179
4
3
Order By: Relevance
“…30 Much of the difference between our estimate of ICER and the substantially higher estimate reported by McMahon et al 31 can be explained by the difference in the number of follow-up CT scans per positive screening examinationapproximately one observed in the NLST, 32 as compared with four assumed in the study by McMahon et al Much of the difference between our estimate and the lower estimate reported by Pyenson et al 33 can be explained by their assumption that the reduction in mortality from lung cancer that resulted from screening would be higher than the 20% observed in the NLST.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…30 Much of the difference between our estimate of ICER and the substantially higher estimate reported by McMahon et al 31 can be explained by the difference in the number of follow-up CT scans per positive screening examinationapproximately one observed in the NLST, 32 as compared with four assumed in the study by McMahon et al Much of the difference between our estimate and the lower estimate reported by Pyenson et al 33 can be explained by their assumption that the reduction in mortality from lung cancer that resulted from screening would be higher than the 20% observed in the NLST.…”
Section: Discussioncontrasting
confidence: 53%
“…The ICER rose substantially when we included future health care costs of survivors that were unrelated to lung cancer, but we did not include these costs in our base case because their inclusion is controversial 12 and because they have not been included in prior cost-effectiveness analyses of lung-cancer screening. [7][8][9][10]31,33,35 The ICER also rose substantially when we increased the costs of the screening examination, follow-up, and surgery and when we reduced the quality of life related to positive screening results and to a diagnosis of stage IA lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The large variations noted among the existing estimates have prohibited researchers and policymakers from drawing a firm conclusion regarding the cost-effectiveness of LDCT screening. [11][12][13][14][15][16] Based on the number needed to screen to prevent 1 death from lung cancer in the NLST, Goulart et al estimated that the additional cost of LDCT screening to avoid 1 lung cancer death is $240,000.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the cost-effectiveness of CT screening depend on assumptions such as the cost of the screening CT, the false-positive rate, the number and type of diagnostic tests and procedures and their costs, the stage distribution of cancers detected, treatment methods and costs, and mortality rates. Whereas previous studies found that the cost per quality-adjusted life year saved would be less than $50,000 (the amount at present generally accepted as the upper limit for being cost-effective) [27,28], studies using NLST data estimate substantially higher costs [29,30]. A pending cost-effectiveness analysis from the NLST, based on cost data collected from actual screening, should provide even more realistic estimates.…”
Section: Ethical Considerationsmentioning
confidence: 94%